Immunostimulatory Potential of Fruits and Their Extracts in Poultry - Hasted, Teri-Lyn; Sharif, Shayan; Boerlin, Patrick; Diarra, Moussa Sory (Frontiers in Immunology, 2021)
The impact of antibiotic use for growth promotion in livestock and poultry production on the rise of antimicrobial resistant (AMR) bacteria led to the ban of this practice in the European Union in 2006 and a restriction of antimicrobial use (AMU) in animal agriculture in Canada and the United States of America. There is a high risk of infectious diseases such as necrotic enteritis due to Clostridium perfringens, and colibacillosis due to avian pathogenic Escherichia coli in antimicrobial-free broiler chickens. Thus, efficient and cost-effective methods for reducing AMU, maintaining good poultry health and reducing public health risks (food safety) are urgently needed for poultry production. Several alternative agents, including plant-derived polyphenolic compounds, have been investigated for their potential to prevent and control diseases through increasing poultry immunity. Many studies in humans reported that plant flavonoids could modulate the immune system by decreasing production of pro-inflammatory cytokines, T-cell activation, and proliferation. Fruits, especially berries, are excellent sources of flavonoids while being rich in nutrients and other functionally important molecules (vitamins and minerals). Thus, fruit byproducts or wastes could be important resources for value-added applications in poultry production. In the context of the circular economy and waste reduction, this review summarizes observed effects of fruit wastes/extracts on the general health and the immunity of poultry.